2000
DOI: 10.1116/1.1286102
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: “Copper electroplating for future ultralarge scale integration interconnection” [J. Vac. Sci. Technol. A 18, 656 (2000)]

Abstract: ERRATA Erratum: ''Copper electroplating for future ultralarge scale integration interconnection'' †J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…The electrical resistivity values of all copper layers are relatively similar as they vary within a range between 3.8 and 5.7 μΩ cm. These values are in accordance with reported values for electroplated (2.0-8.3 μΩ cm) [53] or electroless (3.3-6.2 μΩ cm) [54] copper films. The electrical resistivity of bulk copper is 1.78 μΩ cm.…”
Section: Electrical Properties Of Copper Layerssupporting
confidence: 92%
“…The electrical resistivity values of all copper layers are relatively similar as they vary within a range between 3.8 and 5.7 μΩ cm. These values are in accordance with reported values for electroplated (2.0-8.3 μΩ cm) [53] or electroless (3.3-6.2 μΩ cm) [54] copper films. The electrical resistivity of bulk copper is 1.78 μΩ cm.…”
Section: Electrical Properties Of Copper Layerssupporting
confidence: 92%
“…Additionally, in previous papers, [18][19][20][21] Kelly and coworkers showed that the leveling of 0.2 m trenches by an acid copper electrolyte with polyethylene glycol ͑PEG͒, Cl Ϫ , bis͑3-sulfopropyl͒ disulfide, and Janus Green B. Gau and co-workers demonstrated that copper could be electroplated into a 0.3 m dimension with an aspect ratio of 3 trenches by adding hydroxyl amine sulfate in the electrolyte.…”
Section: B Polarization Effects On Filling Capabilitymentioning
confidence: 99%
“…Secondarily, insulating layer such as SiO 2 is formed by thermal oxidation or vapor deposition (5). For the conductive filling of TSV, copper by electroplating is currently used in terms of cost and performance (6)(7)(8)(9). A diffusion barrier such as TiN is needed to prevent Cu to diffuse into the Si substrate and is formed by vapor deposition over the insulating layer (10).…”
Section: Introductionmentioning
confidence: 99%